Isoliquiritigenin Activates Nuclear Factor Erythroid-2 Related Factor 2 to Suppress the NOD-Like Receptor Protein 3 Inflammasome and Inhibits the NF-κB Pathway in Macrophages and in Acute Lung Injury - Liu, Qinmei; Lv, Hongming; Wen, Zhongmei; Ci, Xinxin; Peng, Liping (Frontiers in Immunology, 2017)
Among the cellular response mechanisms, the nuclear factor erythroid-2 related factor 2 (Nrf2) pathway is considered a survival pathway that alleviates oxidative injury, while both the NLRP3 and NF-κB pathways are pro-inflammatory pathways that cause damage to cells. These pathways are implicated in the development and resolution of acute lung injury (ALI). Isoliquiritigenin, a flavonoid from the liquorice compound, is suggested to be a regulator of the above pathways, but the mechanisms of how the NLRP3/NF-κB pathway interacts with Nrf2 and its protective effects in ALI remain unknown. In the present study, isoliquiritigenin inhibited ROS generation and cytotoxicity induced by t-BHP and pro-inflammatory enzymes production induced by LPS in RAW 264.7 cells. Such cytoprotective effects coincided with the induction of AMPK/Nrf2/ARE signaling and the suppression of the NLRP3 and NF-κB pathways. Consistent with these findings, isoliquiritigenin treatment significantly alleviated lung injury in LPS-induced ALI mice, which was reflected by reductions in histopathological changes, pulmonary edema and protein leakage. At the same time, the increased levels of inflammatory cell exudation and pro-inflammatory mediators, the enhanced production of ROS, MPO and MDA and the depleted expression of GSH and SOD induced by LPS were ameliorated by isoliquiritigenin. Furthermore, isoliquiritigenin notably activated AMPK/Nrf2/ARE signaling and inhibited LPS-induced NLRP3 and NF-κB activation in the lung. Moreover, although inhibition of the LPS-induced histopathological changes and ROS production were attenuated in Nrf2-deficient mice, the repression of the NLRP3 and NF-κB pathways by isoliquiritigenin was Nrf2-dependent and Nrf2-independent, respectively. In conclusion, our results are the first to highlight the beneficial role and relevant mechanisms of isoliquiritigenin in LPS-induced ALI and provide novel insight into its application.